2002
DOI: 10.1039/b203652p
|View full text |Cite
|
Sign up to set email alerts
|

On the structure of Li3Ti2(PO4)3

Abstract: International audienceThe structure of the Nasicon-type phase Li3Ti2(PO4)3, obtained by chemical lithiation of LiTi2(PO4)3, has been characterised using neutron diffraction for the long range structure and 7Li NMR for more local information. The lithium atoms were precisely located from the neutron diffraction data, using nuclear difference Fourier maps. The lithium ions, which were known to be in the large M2 cavity, occupy two M3 and M′3 subsites (distorted tetrahedra) with occupation factors of 2/3 and 1/3,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
133
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(151 citation statements)
references
References 31 publications
13
133
0
Order By: Relevance
“…Pure LTP sample powder is white in colour while Mn doped samples are light gray colored and as Mn concentration increased the colour intensity also increased from light gray to thick gray. Lattice parameters of LTP calculated from the XRD data listed in Table 1 agree with earlier reports of crystallographic data [11][12][13] . Raman spectra of LTP and Mn doped LTP samples are shown in Figure 3 from which, it can be seen that four intense peaks appear at 967, 986, 1005 and 1038 cm -1 along with two other peaks at 1070 and 1092 cm -1 .…”
Section: Resultssupporting
confidence: 78%
“…Pure LTP sample powder is white in colour while Mn doped samples are light gray colored and as Mn concentration increased the colour intensity also increased from light gray to thick gray. Lattice parameters of LTP calculated from the XRD data listed in Table 1 agree with earlier reports of crystallographic data [11][12][13] . Raman spectra of LTP and Mn doped LTP samples are shown in Figure 3 from which, it can be seen that four intense peaks appear at 967, 986, 1005 and 1038 cm -1 along with two other peaks at 1070 and 1092 cm -1 .…”
Section: Resultssupporting
confidence: 78%
“…Deviations form this symmetry were reported for lithium-excess compounds, e.g. Li 3 Ti 2 (PO 4 ) 3 , in which two types of crystallographic sites are available for Li [26]. These two sites are partially occupied and such vacant sites represent a favourable condition to promote Li diffusion in the system (Fig.…”
Section: Nasicon-type Li-ion Conductorsmentioning
confidence: 90%
“…Crystallographic structures have been reported for compounds based on tetravalent hafnium, titanium, germanium and tin and in every case a high temperature phase has been reported with rhombohedral symmetry that suggests the formation of phases isostructural with a-LiZr 2 (PO 4 ) 3 . [99][100][101][102] Whilst this is broadly correct there remain some differences in the crystallographic models used to describe these structures. For example a characterisation of a sample described as 'LiHf 2 (PO 4 ) 3 ' identified the presence of disordered lithium cations in the elongated octahedral site occupied in the a LiZr 2 (PO 4 ) 3 structure, but could not identify any additional lithium in the structure and concluded that the negative charge of the anionic framework was balanced by a small quantity of extra-framework hafnium.…”
Section: Doped Analogues Of Lizr 2 (Po 4 )mentioning
confidence: 99%